Pelatihan Efikasi Diri untuk Menurunkan Stres Kerja Pada Anggota Polri Ditsabhara Polda DIY - Andy Arciana Dodik Setyawan Sukma; Kamsih Astuti; Siti Noor Fatmah (LPPM Universitas Proklamasi 45, 2018)
Objective of this study is to understand the influence of self-efficacy training on decreasing work stress among 22 policemen in Yogyakarta. They worked as the community protectors. They were divided randomly into 2 groups i.e. the experiment group (11 policemen) and the control group (11 policemen). The experimental design was the pretest-posttest control group. For this research, we created two instruments to measure the independent and dependent variables respectively i.e. the self-efficacy scale and the work stress scale, and the intervention was the self-efficacy improvement training. The research data were analyzed based on the Wilcoxon Rank Test (to understand the difference of work stress level between the pre-test and posttest groups) and the U-Mann Whitney statistical techniques (to understand the difference of work stress scores between the post-test experiment and control groups. The first hypothesis was confirmed that the Wilcoxon Rank Test Z score = -2.936 (p = .003) was significant. In other words, the work stress level at the post-test ( = 113,91) was much higher because of self-efficacy training than the pre-test ( = 49,09). The second hypothesis was also confirmed that the U-Mann Whitney Z score = -3.977, p = .000 (p<.001) was very significant. In other words, the work stress level at the post-test experiment group ( = 49.09) was much lower than the control group ( = 112.55). Key words: Work Stress, Self-Efficacy Training, Policeman